Arthroscopic Rotator Cuff Repair Results in Lower Two-Year Reoperation Rates Compared With Open Rotator Cuff Repair in a Large Cross-sectional Cohort - Nicole M. Truong, B.S; Nicolas Cevallos, B.S; Drew A. Lansdown, M.D; C. Benjamin Ma, M.D; Brian T. Feeley, M.D; Alan L. Zhang, M.D (Elsevier, 2021)
Purpose: To use a large, contemporary database to perform a cross-sectional analysis of current practice trends in rotator cuff repair (RCR) for the treatment of full-thickness rotator cuff tear (RCT) and determine outcomes of arthroscopic and open RCR, including hospital readmissions and 2-year reoperation rates with accurate laterality tracking using International Classification of Diseases, Tenth Revision (ICD-10) codes. Methods: The PearlDiver Mariner dataset was used to query patients with full-thickness RCTs from 2010 to 2017. Propensity-score matching was performed to account for differences in age and comorbidities and allow for comparison between those undergoing open RCR and arthroscopic RCR. Subsequent procedures were tracked using ICD-10 codes to identify ipsilateral surgery within 2 years of index surgery. Hospital and emergency department admission within 30 days of surgery were investigated. Results: Of 534,076 patients diagnosed with full-thickness RCT, 37% underwent RCR; 73% of which were arthroscopic. From 2010 to 2017, arthroscopic RCRs increased from 65% to 80%, whereas open RCRs decreased from 35% to 20% (P < .0001). Younger patients underwent arthroscopic RCR more frequently, and patients who underwent open RCR had greater rates of 30-day emergency department (7.0%) and hospital readmission (2.0%) compared with arthroscopic RCR (6.3%, 1.0%, respectively) (P < .0001). For 24,392 patients with ICD-10 coding and 2-year follow-up, 10.4% of patients required reoperation, with the most common procedure being revision RCR, and 1.3% required conversion to arthroplasty. Open RCRs were more likely to require subsequent surgery (11.3%) compared with arthroscopic RCR (9.5%) (P < .0001). Patients aged 50 to 59 had the greatest rate of reoperation (14.0%), but no patients younger than age 40 years required reoperation, and no patients younger than age 50 years required conversion to arthroplasty. Conclusions: The frequency of arthroscopic RCR has continued to increase compared to open RCR. In this large cross-sectional analysis, arthroscopic RCR demonstrated lower 2-year reoperation rates and 30-day readmission rates compared to open RCR. Level of Evidence: III, cross-sectional study.